Pd-Catalysed [3 + 2]-cycloaddition towards the generation of bioactive bis-heterocycles/identification of COX-2 inhibitors via in silico analysis - Ansari, Arshad J. (Royal Society of Chemistry, 2022)
In the current research, we envisaged the synthesis of bis-heterocycles containing the dihydroisoxazole ring by [3 + 2] cycloaddition of VECs (vinyl ethylene carbonates) and nitrile oxides, assisted by a Pd catalyst. Herein we explored hydroximoyl chlorides as versatile precursors for the in situ generation of nitrile oxides that were exploited to achieve the cycloaddition reaction on a vinyl group of VECs to generate bis-heterocycles. In silico-based studies of bis-heterocycles on the cyclooxygenase (COX) enzyme displayed selective COX-2 inhibition.
Only IISER Mohali authors are available in the record.
Keywords: Pd-Catalysed [3 + 2]-cycloaddition; identification of COX-2; silico analysis